Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3233/tad-2011-0331
|View full text |Cite
|
Sign up to set email alerts
|

Factors that impact the level of difficulty of everyday technology in a sample of older adults with and without cognitive impairment

Abstract: Nygård. Factors that impact the level of difficulty of everyday technology in a sample of older adults with and without cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
(33 reference statements)
0
33
0
1
Order By: Relevance
“…It may also reflect that these ETs were incorporated to a greater extent into the everyday activities and habits of the participants [36]. It has earlier been demonstrated that ETs used daily or weekly are less challenging for this sample than those that are used more seldom [14]. However, some of these less challenging ETs such as stove and shaver were in this study perceived as more challenging than they were observed.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…It may also reflect that these ETs were incorporated to a greater extent into the everyday activities and habits of the participants [36]. It has earlier been demonstrated that ETs used daily or weekly are less challenging for this sample than those that are used more seldom [14]. However, some of these less challenging ETs such as stove and shaver were in this study perceived as more challenging than they were observed.…”
Section: Discussionmentioning
confidence: 71%
“…These ETs are often intuitive to the user and require less cognitive effort [14]. The less challenging ETs could also be described as being more common and well-known technologies, and the participants may therefore have been more experienced in using them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations